Handbook of Special Tests in Musculoskeletal Examination : An evidence-based guide for clinicians - Paul Hattam (London : Elsevier, 2020)
"Despite growing reliance on imaging, clinical examination remains the bedrock of diagnosis of the musculoskeletal patient. Special tests have widespread utility particularly in sport and can often help to elucidate a patient's presentation where the lesion is subtle and otherwise difficult to detect and, in turn, guide management and treatment. Special Tests in Musculoskeletal Examination 2nd Edition is a pocketbook guide to over 100 peripheral tests." --Amazon.ca
Keywords: Diagnostic Techniques and Procedures; Musculoskeletal system Examination Handbooks, manuals, etc; Evidence-Based Medicine methods